Praxeological evaluation of the efficiency in offensive activities of the individual football players as a determinant in rationalizing and shaping a sports game - Duda, H.; Mucha, D.; Ambrozy, T.; Omorczyk, J.; Makuch, R.; Mucha, D. (Baltic Journal of Health and Physical Activity, 2018)
Background: The article has a developmental character (application); it raises problems connected with an objective assessment of an individual game.